Pengaruh Experiential Marketing dan Zoo Image terhadap Revisit Intention dengan Experiential Satisfaction sebagai Variabel Intervening - Viyo Tri Taraoktavia; Tias Andarini Indarwati (Jurnal Ilmu Manajemen, 2021)
The sustainability of a tourist attraction is reflected by the experiential satisfaction of visitors to tourism objects. One of the influencing factors is to create engaging experiential marketing and make an impression on the visitor's mind and the image attached to the company. Experiencing engaging experiential marketing and a good image from the company makes visitors feel experiential satisfaction and revisit intention. This study aims to determine the effect of experiential marketing and zoo image on revisit intention with experiential satisfaction as an intervening variable. This study used 200 samples with a non-probability sampling technique using the purposive sampling method. Data were collected using an online questionnaire. The analytical tool in this research is path analysis using AMOS and IBM SPSS. Based on the study results, experiential marketing positively affects experiential satisfaction and revisit intention directly, unlike the zoo image, which positively affects experiential satisfaction but not revisit intention. As a suggestion, Surabaya Zoo can improve visitors' image, such as improving the services provided and adding engaging experiential marketing to attract visitors' engagement again in the future.